Buss’ mate choice theory - CHOY, Bryan K. C. (Institutional Knowledge at Singapore Management University, 2021)
Buss and Schmitt’s (1993) sexual strategies theory (SST) is a predominant evolutionary framework for understanding human mate preferences. SST proposes that mate preferences represent coherent suites of psychological mechanisms that have evolved to solve adaptive problems faced by humans in the pursuit of short- and long-term relationships, are sex-differentiated, and are context-dependent.